Quelques effets du confinement sur la construction des inégalités scolaires - Julien Netter (Nantes Université, 2022)
The distance learning implemented during the spring 2020 lockdown resulted in an increase in educational ine-qualities in French primary schools. A sociologically oriented ethnographic research conducted before, during and since the confinement with primary school teachers in Seine-Saint-Denis allows us to grasp the forced transfor-mations of teachers' practices that could explain, at least to some degree, such an increase. The difficulty of main-taining the construction of shared meanings, the transformation of the systems of signs used for interactions with pupils, the fragility of the 'autonomy' required of pupils and the inequality of their parents in terms of supervision of personal work, and the difficulties in maintaining learning assistance are all phenomena that have sometimes ac-cumulated, making the benefit of work situations uncertain for some students.